2006
DOI: 10.1071/sr05042
|View full text |Cite
|
Sign up to set email alerts
|

The influence of season, agricultural management, and soil properties on gross nitrogen transformations and bacterial community structure

Abstract: The aim of this study was to assess the influence of season, farm management (organic, biodynamic, integrated, and conventional), and soil chemical, physical, and biological properties on gross nitrogen (N) fluxes and bacterial community structure in the semi-arid region of Western Australia. Moisture availability was the dominant factor mediating microbial activity and carbon (C) and N cycling under this climate. In general, microbial biomass N, dissolved organic N, and potentially mineralisable N were greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 51 publications
5
33
1
2
Order By: Relevance
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…Seasonal and other temporal alternations in climatic conditions are determinants of soil N cycle dynamics (Cookson et al, 2006;Wolsing and Priemé, 2004;Horz et al, 2004). Soil N cycling includes both reductive and oxidative processes, in which soil microbes have a predominant role (Cabello et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biological nitrification is the key process by which N turnover and N removal from agricultural ecosystems occurs (e.g. Vitousek et al, 1979;Currie, 1996;Müller et al, 2004b;Cookson et al, 2006). Nitrification is known to promote nitrogen eluviation from soils, because the less mobile cation ammonium (NH + 4 ) is oxidised by nitrifiers to the much more mobile anion nitrate (NO − 3 ) (Abbasi and Adams, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Esto puede explicarse por la dominancia de las formas nítricas debido a la adición de fertilizantes y a la mayor disponibilidad de NO 3 - (Cookson et al, 2006). Tanto para el tratamiento orgánico como para el convencional, las concentraciones medias de NO 3 -y Nmin en el agua de escorrentía disminuyeron al pasar del año 2001 al 2010; en contraste, la concentración de NH 4 + incrementó ligeramente, siendo mayor el aumento en el tratamiento convencional.…”
Section: Concentracionesunclassified
“…By analyzing the effect of plot management on runoff water, Table 1 shows that the mean concentrations of NO 3 -in 2001 and 2010 were higher in plots with CM compared to those with OM. This can be explained by the dominance of nitric forms due to the addition of fertilizers and the greater availability of NO 3 - (Cookson et al, 2006). + en la precipitación son mayores que las de NO 3 -, lo que está ligado a una mayor emisión de nitrógeno por actividades relacionadas con la urbanización (Galloway, Likens, & Hawley, 1984).…”
Section: Concentracionesmentioning
confidence: 99%